Peningkatan Kapasitas Inovasi dan Presentasi Proyek produk Mahasiswa dalam Exchibition Internasional iPROPEX 2024 - Cut Evawani; Desti Umita Sari Sikumbang; Zulkarnaini; Sonia Ulfa; Zubaili; Khatijah; Nurasyiah (PASAI : Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to explore the enhancement of innovation capacity and presentation skills of student product projects in the International Exhibition iPROPEX 2024. Through the development of innovative products and intensive training in presentation skills, students are encouraged to create creative ideas that not only meet global market needs but also have the potential to compete internationally. A significant achievement was the product Meuseukat Geutanyo, which won a silver medal, demonstrating that the applied innovation approach had a positive impact on students’ ability to compete on a global level. The results of this study indicate that improving technical skills, entrepreneurship, and effective communication skills plays a key role in students' success in international competitions. Overall, this research provides insights into how capacity-building strategies can prepare students to face challenges in the global industry and entrepreneurship world.